Tingkat Validitas Media Bapaguh untuk Pembelajaran Tembang Macapat Gambuh Siswa Kelas IV SD - Muna, Syarifatul; Fardani, Much Arsyad; Bakhruddin, Ahmad (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Learning media is very important in the learning process. One example of the use of learning media today is Android-based media. The use of Android-based media as a learning medium is very important in the process of achieving learning objectives. With a variety of interesting learning media, it can increase students' motivation and interest in learning. However, what happens in the practice of learning macapat songs in elementary schools is that teachers have not utilized technological developments as a learning medium. The teacher only uses LKS media as a learning medium for the Macapat Gambuh song. This research aims to develop and measure the level of validity of Android-based media in the form of Bapaguh media for learning the Macapat Gambuh song. This research method uses Research and Development with the ADDIE (Analyze, Design, Development, Implementation, Evaluate) development model. The level of appropriateness of Bapaguh media can be determined by measuring the level of validity of the media by media expert validators, material experts and language experts with validation results of 98%, 88% and 94%. Based on the validation results, it can be concluded that the Bapaguh media is very suitable to be developed as a learning medium for the Macapat Gambuh song material.Â